A Comprehensive Treatment Protocol for Endometriosis Patients Decreases Pain and Improves Function - Shrikhande A; Patil S; Subhan M; Moody E; Natarajan J; Tailor Y; Mamsaang M; James N; Leishear K; Vyas R; Sandhu S; Ahmed T; et al. (Dove Medical Press, 2023)
Allyson Shrikhande,1,2 Soha Patil,1,2 Merzia Subhan,1,2 Erika Moody,1,2 Janaki Natarajan,1,2 Yogita Tailor,1,2 Marjorie Mamsaang,1,2 Neha James,1,2 Kimberlee Leishear,1,2 Rakhi Vyas,1,2 Sandra Sandhu,1,2 Tayyaba Ahmed,1,2 Rosemarie Filart,1,2 Gabrielle Daniel,1,2 Iris Kerin Orbuch,3,4 Yaniv Larish,1,2 Lora Liu1,2 1Pelvic Rehabilitation Medicine Clinical Research Foundation, West Palm Beach, FL, USA; 2The Feinstein Institute for Medical Research, Manhasset, NY, USA; 3Providence St John's Hospital, Santa Monica, CA, USA; 4Advanced Gynecologic Laparoscopy Center, Los Angeles, CA, USACorrespondence: Allyson Shrikhande, Email AShrikhande@pelvicrehabilitation.comPurpose: The purpose of this paper is to evaluate the efficacy of a multimodal, outpatient neuromuscular protocol in treating remaining sensitization and myofascial pain in endometriosis patients post-surgical excision.Patients and Methods: A retrospective longitudinal study was conducted for women aged 22 to 78 with a history of surgically excised endometriosis. 60 women with an average duration of pain of 8.63 ± 7.65 years underwent a treatment protocol consisting of ultrasound guided trigger point injections, peripheral nerve blocks, and pelvic floor physical therapy for 6 weeks. Concomitant cognitive behavioral therapy once weekly for a total of 12 weeks was also undertaken. Pain intensity and pelvic functionality were assessed at new patient consults and 3-month follow ups using Visual Analogue Scale (VAS) and Functional Pelvic Pain Scale (FPPS).Results: At new patient consults, average VAS and FPPS were 7.45 ± 2.11 (CI 6.92- 7.98) and 14.35 ± 6.62 (CI 12.68 − 16.02), respectively. At 3-month follow ups, average VAS and FPPS decreased to 4.12 ± 2.44 (CI 3.50- 4.73; p < 0.001) and 10.3 ± 6.55 (CI 8.64- 11.96; p < 0.001), respectively. Among FPPS categories, sleeping, intercourse, and working showed the highest statistical significance.Conclusion: Data suggests the multimodal protocol was effective in treating the remaining underlying sensitization and myofascial pain seen in Endometriosis patients post-surgical excision, particularly in decreasing pain and improving function during work and intercourse.Keywords: chronic pelvic pain, peripheral sensitization, central sensitization, myofascial dysfunction